Aluminum corrosion–passivation regulation prolongs aqueous batteries life - Binghang Liu; Tianshi Lv; Anxing Zhou; Xiangzhen Zhu; Zejing Lin; Ting Lin; Liumin Suo (Nature Communications, 2024)
Abstract Aluminum current collectors are widely used in nonaqueous batteries owing to their cost-effectiveness, lightweightness, and ease of fabrication. However, they are excluded from aqueous batteries due to their severe corrosion in aqueous solutions. Here, we propose hydrolyzation-type anodic additives to form a robust passivation layer to suppress corrosion. These additives dramatically lower the corrosion current density of aluminum by nearly three orders of magnitude to ~10−6 A cm−2. In addition, realizing that electrochemical corrosion accompanies anode prelithiation, we propose a prototype of self-prolonging aqueous Li-ion batteries (Al ||LiMn2O4 ||TiO2), whose capacity retention rises from 49.5% to 70.1% after 200 cycles. A sacrificial aluminum electrode where electrochemical corrosion is utilized is introduced as an electron supplement to prolong the cycling life of aqueous batteries. Our work addresses the short-life issue of aqueous batteries resulting from the corrosion of the current collector and lithium loss from side reactions.